1998
DOI: 10.1038/sj.gt.3300762
|View full text |Cite
|
Sign up to set email alerts
|

The selectable marker neo gene down-regulates gene expression from retroviral vectors containing an internal ribosome entry site

Abstract: The internal ribosome entry site (IRES) from the picornaterial neo sequence has a negative effect on expression. virus family has frequently been used to express multiple Analysis of the steady-state RNA levels isolated from genes from a polycistronic message in retroviral vectors.transfected packaging cells showed that the neo-containWhile examining factors affecting levels of gene expression ing retroviral vectors produced significantly lower levels of in IRES-containing retroviral vectors, it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…31,32 On the other hand, sequences other than those present in the LTR can influence viral transcription. 33 Indeed, the pBH vectors contain sequence elements, such as the hygromycin resistance gene and a prokaryotic origin of DNA replication, 12 that may contribute to the negative reciprocal interactions that results in poor or absent gp91-gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 On the other hand, sequences other than those present in the LTR can influence viral transcription. 33 Indeed, the pBH vectors contain sequence elements, such as the hygromycin resistance gene and a prokaryotic origin of DNA replication, 12 that may contribute to the negative reciprocal interactions that results in poor or absent gp91-gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other mechanisms that could play a contributory role to our observed loss of gene expression have also been reported. For example, expression of the neomycin resistance gene has been linked to problems with gene expression 4143. Although we cannot directly exclude any of these mechanisms as contributory, our results suggest either (1) a problem directly associated with the SRα promoter's ability to maintain gene expression in vivo on murine T cells or (2) a problem indirectly related to the SRα promoter gene position in the specific retroviral construct used in these studies.…”
Section: Discussionmentioning
confidence: 79%
“…Again, MT‐IDS gave the highest level of IDS activity, on average 2‐ and 4‐fold higher levels than MIN‐IDS and two other vectors, respectively (Figure 3B). These results suggested that even the same LTR could give varying results when placed under different genomic environments, consistent with our previously published data 24.…”
Section: Resultsmentioning
confidence: 90%